Digital literacy and research agenda: A conceptual analysis - Md Hafizi Ahsan; Saidatul Akmar Ismail; Masitah Ahmad (ResearchGate, 2022)
Introduction: Post-crisis of COVID19 contributes rapidly the changing of every aspects of human society’s quality of life. More life survival skills are needed in order to ensure sustainability. Objectives: This paper attempts to analyse digital literacy based on previous literature and to suggest the research agenda. Methods: This paper opts the conceptual analysis of digital literacy related literature in order to uncover the key themes of research. The term, digital literacy is found to have conceptualised from many ideas, meanings, and contexts especially during the digital era. It is evolving, related to many various terms, and thus always requiring new research agenda to add substantial values to the field. Results: Based on the previous literature, the main finding suggests three immediate research agenda; the need to update the concept, to focus the research on the socio-emotional and psychological aspects of students upon the development of their digital literacy and the need to conduct studies on the indigenous and older adult groups. Conclusions: This paper attempts to discuss the conceptual analysis of digital literacy based on previous literature and to suggest the research agenda. The term, digital literacy is found to have conceptualised from many ideas, meanings, and contexts especially during the digital era. It is evolving, related to many various terms, and thus always requiring new research agenda to add substantial values to the field. Based on the previous literature, we suggest three immediate research agenda; the need to update the concept, to focus the research on the socio-emotional and psychological aspects of students upon the development of their digital literacy and the need to conduct studies on the indigenous and older adult groups.